Distribution of Secanting Rice to Underprivileged Families in Bintan Regency - Saputra, Haidir; Darmawan, Ikhsan; Suryaningsih, Suryaningsih (PT FORMOSA CENDEKIA GLOBAL, 2025)
Poverty, being a major problem in Bintan Regency, hampers people's access to their basic food needs. The purpose of the